The impact of Muslim and Christian religious leaders responding to COVID-19 in Israel - Essa-Hadad, Jumanah; Abed Elhadi Shahbari, Nour; Roth, Daniel; Gesser-Edelsburg, Anat (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic is one of the most significant public health emergencies in decades and has affected all countries worldwide. Religious leaders have been recognized as playing a pivotal role in health promotion during times of crisis. This study explored the role that Muslim and Christian religious leaders played in Israel during the pandemic, and the impact that their activities had on the community. Methods A qualitative study involving semi-structured interviews was conducted with Muslim and Christian religious leaders and health policy makers from the Arab community. Intensive purposeful sampling was used to locate the two target audiences. Interview protocols were developed and included questions about the role they played during the pandemic, challenges they faced, and dialogue and partnerships they had. Interviews were audio-recorded, transcribed, and analyzed using thematic content analysis. Results Ten Muslim Sheikhs, three Christian clergy, and four health policy makers were interviewed. Religious leaders played a predominant role in promoting health during the COVID-19 crisis. Both religious leaders and health policy makers reported similar challenges including dealing with fake news and the conspiracy theory, social events and gatherings, frustrations about gaps in policy toward religious institutions, and lack of trust toward State. Health policy makers recognized the key role religious leaders played and emphasized the importance of engaging religious leaders. Conclusion The COVID-19 pandemic has been a catalyst for partnership between health policy makers and religious leaders. Religious leaders should play an integral and integrated role in promoting health during future health crises, not only in implementation of guidelines but also in development of policy so that the guidelines are tailored and sensitive to specific communities to avoid conflicts. As trusted authorities, religious leaders serve as a bridge between health authorities and communities and can be mediators who reconcile science, policy and religious perspectives. The routine cooperation between decision makers, opinion leaders, and religious leaders as social gatekeepers can increase the public's level of trust in the system.